EFEKTIFITAS PENGGUNAAN MEDIA POSTER DAN LEAFLET DALAM PENDIDIKAN KESEHATAN REPRODUKSI TERHADAP PENINGKATAN PENGETAHUAN MASYARAKAT DI KABUPATEN BELU - Indriati Andolita Tedju Hinga (CHMK Applied Science Journal, 2019)
Belu Regency is geographically bordered directly by the state of Timor Leste, so that it has the potential as an entry point for disease transmission. The case of HIV-AIDS in Belu Regency ranks second highest in NTT Province. Reproductive health education needs to be given to the community early on. This study aims to determine the effectiveness of the use of poster and leaflet media in reproductive health counseling to increase public knowledge. The target group of counseling in this study were children, adolescents and parents in Fohoeka Village. Fohoeka Village is one of the villages in Belu Regency which borders directly with the State of Timor Leste. The method used is a pre-experimental research design with one-group pretest posttest. The sampling technique used was Simple Random Sampling of 180 respondents (children, adolescents and parents of 60 people each). Data were analyzed using paired-sample T-test. The results of this study indicate that the use of leaflet and poster media in reproductive health education is effective in increasing knowledge in children, adolescents and parents with a significance value (ρ)0,00<(α)0,05 and (ρ)0,02<(α)0,05. Reproductive health education with the lecture method is more effective by adding media aids such as posters, leaflets and so on. Media-based health education is very effective to be recommended in every disease prevention and management program in the community. Keywords: Media, Reproductive Health Education, Community.